Social Behavior Communication Change (SBCC) for Handling Infectious Diseases in Bandung - O. Solihin; Y. Mogot; M. Madonna (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The rapid and widespread spread of infectious disease outbreaks in society is influenced by two main factors, namely physical conditions and behavior (behavior). Infectious disease is an epidemic that is being handled seriously by the Bandung City Government, West Java Province. This study examines the Social Behavior Communication Change (SBCC) approach which concentrates on behavior to facilitate individuals, households, groups, and communities in adopting and maintaining practices related to improving health and nutrition. Objective: The research intends to describe the communication program for handling infectious diseases in the city of Bandung using the SBCC approach. Methods: descriptive qualitative research by conducting a systematic literature review (systematic review) in the form of a conceptual study of the condition of infectious diseases in the city of Bandung, Social Behavior Communication Change (SBCC), the SBCC framework, and the Strategy for Handling Infectious Diseases. Concept definitions are obtained through searching primary data sources in the form of journals and other scientific references. Result: The handling of the outbreak can be done through three main strategies, namely Advocacy, social mobilization, and behavior change communication. Advocacy is in the form of enforcing policy commitments and supporting collaboration with the mayor, parliament, Health Service, Sub-district in Bandung. In the form of social service activities and free medical treatment. For community or social mobilization, the Bandung city government involves health cadres, community leaders, and religious leaders. As well as behavior change communication, namely informing and approaching the patient, the patient's family and the community in the surrounding environment. The conclusion is that the handling of infectious diseases can be done through collaboration between the government and the community through advocacy strategies, social mobilization and communication for social change